1.(а + 2)(а + 6) + (а - 3)(а - 4), при а = 7 2.Решить :(х - 2)(х - 3) - (х + 1)(х - 4) =...

0 голосов
31 просмотров

1.(а + 2)(а + 6) + (а - 3)(а - 4), при а = 7 2.Решить :(х - 2)(х - 3) - (х + 1)(х - 4) = 0 3. Найдите значение выражения: 1 - (- а + 4)(9 - а) - (а + 3)(а - 5), при а = - 10 СРОЧНО!


Математика (28 баллов) | 31 просмотров
Дано ответов: 2
0 голосов

Ответ:


Пошаговое объяснение:

1.(а + 2)(а + 6) + (а - 3)(а - 4), при а = 7

=a²+6a+2a+12+a²-4a-3a+12=2a²+a+24

2*7²+7+24=2*49+31=129

2.Решить :(х - 2)(х - 3) - (х + 1)(х - 4) = 0

х²-3х-2х+6-х²+4х-х+4=0

-2х+10=0

-2х=-10

х=-10:(-2)

х=5


(123k баллов)
0 голосов

Ответ:

(а + 2)(а + 6) + (а - 3)(а - 4), при а = 7

=a²+6a+2a+12+a²-4a-3a+12=2a²+a+24

2*7²+7+24=2*49+31=129

(х - 2)(х - 3) - (х + 1)(х - 4) = 0

х²-3х-2х+6-х²+4х-х+4=0

-2х+10=0

-2х=-10

х=-10:(-2)

х=5

Пошаговое объяснение:


(114 баллов)